1992
DOI: 10.1128/jvi.66.7.4576-4579.1992
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 large T-antigen function is required for induction of tetraploid DNA content during lytic infection

Abstract: Infection of quiescent CV-1 cells with simian virus 40 mutant tsA30 at 37°C resulted in the induction of two rounds of cellular DNA synthesis in T-antigen-positive cells, as previously described for wild-type simian virus 40. Following infection with tsA30 at 40.5°C, T-antigen-positive cells were induced into S phase and reached a diploid G2 DNA content; however, a second S phase was not initiated. The failure of tsA30-infected CV-1 cells to enter tetraploid S phase at 40.5°C identifies a T-antigen function, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…4), the cell population could move past the block and through the cell cycle as a synchronous cohort. Consistent with the idea that Tag can cause a transient cell cycle block, Tag expression has been shown to prevent mitosis during productive SV40 infection of monkey cells (5,24). In addition, we previously showed that Tag expression lengthens G 2 ϩ M cell cycle phase duration (28).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…4), the cell population could move past the block and through the cell cycle as a synchronous cohort. Consistent with the idea that Tag can cause a transient cell cycle block, Tag expression has been shown to prevent mitosis during productive SV40 infection of monkey cells (5,24). In addition, we previously showed that Tag expression lengthens G 2 ϩ M cell cycle phase duration (28).…”
Section: Discussionsupporting
confidence: 80%
“…Flow cytometric detection of viral gene expression in infected cells has been used to quantify virus number (4,8,21,30), to examine viral gene expression during the course of infection (4,14), and to evaluate the cellular phenotypes produced by expression of viral genes (5).…”
mentioning
confidence: 99%
“…As a result, the number of surface-exposed large T molecules varied among different SV40-transformed cell lines derived from different species (Table 1 ). In the case of the murine cell line C57SV, the number of large T molecules per cell depended remarkably on the density of the culture used to prepare the cells, most probably reflecting the influence of the cell cycle on cell surface large T molecule frequency (6,16,19,23). Correlation of virus-specific fluorescence signals with cell-cycle phases has been previously shown for methanol-fixed murine SV40-infected CV-1 cells (6,19).…”
Section: Resultsmentioning
confidence: 74%
“…To determine the number of cells expressing T antigen, the cells were grown on coverslips, fixed with 70% acetone and 30% methanol at -20"C, and stained by indirect immunofluorescence with a polyclonal antibody described by Silver et al (18). The CV-1 cells, SV40 virus, and the infection procedure have been described previously (6,7,15).…”
Section: Methodsmentioning
confidence: 99%
“…When DNA content analyses were performed with flow cytometry, both permissive and nonpermissive cells are induced into multiple rounds of DNA synthesis without mitosis which produce a cell with a >G, DNA content (tetraploid S and tetraploid G,/M) (11,(14)(15)(16). Further, a temperature-sensitive mutant of SV40, tsA 30, was unable to initiate a second round of DNA synthesis a t the nonpermissive temperature (405°C) identifying a T antigen function necessary to bypass G,/M controls and initiate a second round of DNA synthesis (6).…”
mentioning
confidence: 99%